2017
DOI: 10.1002/anie.201706788
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Highly Selective Cell‐Active Inhibitor of the Histone Lysine Demethylases KDM2/7

Abstract: Histone lysine demethylases (KDMs) are of critical importance in the epigenetic regulation of gene expression, yet there are few selective, cell‐permeable inhibitors or suitable tool compounds for these enzymes. We describe the discovery of a new class of inhibitor that is highly potent towards the histone lysine demethylases KDM2A/7A. A modular synthetic approach was used to explore the chemical space and accelerate the investigation of key structure–activity relationships, leading to the development of a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…SPE-MS requires only small amounts of substrates/enzymes for analysis and has been successfully applied to monitoring the activity of 2OG oxygenases by measuring mass shifts, i.e. +16 Da for hydroxylation and -14 Da for demethylation (41)(42)(43)(44)(45). We aimed to combine SPE-MS with the use of stable substrate analogues in which the non-canonical Cys 3-4 EGFD disulfide bond was replaced with a stable thioether.…”
Section: Development Of An Efficient Asph Activity Assaymentioning
confidence: 99%
“…SPE-MS requires only small amounts of substrates/enzymes for analysis and has been successfully applied to monitoring the activity of 2OG oxygenases by measuring mass shifts, i.e. +16 Da for hydroxylation and -14 Da for demethylation (41)(42)(43)(44)(45). We aimed to combine SPE-MS with the use of stable substrate analogues in which the non-canonical Cys 3-4 EGFD disulfide bond was replaced with a stable thioether.…”
Section: Development Of An Efficient Asph Activity Assaymentioning
confidence: 99%
“…However, the lack of ideal inhibitors to KDM2A limits the potential amplification of KDM2A-based therapy. Recent discovery of highly selective inhibitor of KDM2A might provide opportunities to develop KDM2A targeted therapy for lung cancer [ 107 ].…”
Section: Kdms and Their Roles In Lung Cancermentioning
confidence: 99%
“…Prior studies, based on either single-locus or genome-wide gene expression analysis, have suggested that KDM7A is involved in the regulation of target genes downstream of the NF-κB pathway ( Higashijima et al, 2020 ) and the Wnt/β-catenin pathway ( Yang et al, 2019a ; Liu et al, 2020 ), which allude to a broader promalignancy mechanism. Small-molecule inhibitors of KDM7A have been discovered although their therapeutic potentials in breast cancer have yet to be explored ( Gerken et al, 2017 ). Our report as summarized here undoubtedly provides a strong rationale for considering these compounds as a viable treatment option for the most malignant forms of breast cancer.…”
Section: Discussionmentioning
confidence: 99%